Increasing the efficiency of CRISPR‐Cas9‐VQR precise genome editing in rice - Hu, Xixun (Plant Biotechnol J, 2017)
Clustered regularly interspaced short palindromic repeats‐associated protein 9 (CRISPR‐Cas9) is a revolutionary technology that enables efficient genomic modification in many organisms. Currently, the wide use of Streptococcus pyogenes Cas9 (SpCas9) primarily recognizes sites harbouring a canonical NGG protospacer adjacent motif (PAM). The newly developed VQR (D1135V/R1335Q/T1337R) variant of Cas9 has been shown to cleave sites containing NGA PAM in rice, which greatly expanded the range of genome editing. However, the low editing efficiency of the VQR variant remains, which limits its wide application in genome editing. In this study, by modifying the single guide RNA (sgRNA) structure and strong endogenous promoters, we significantly increased the editing efficiency of the VQR variant. The modified CRISPR‐Cas9‐VQR system provides a robust toolbox for multiplex genome editing at sites containing noncanonical NGA PAM.